Adapting in the Arctic: Comparing Functional Adaptation in the Long Bone Diaphyses of Alaskan Hunter-Gatherers - Rosa, Emily R (2019)
This thesis compares cross-sectional geometric measures of femoral, tibial, humeral, and radial diaphyseal robusticity and compares humeral and radial bilateral asymmetry between three samples of native Alaskan hunter-gatherers with different subsistence strategies and resultant levels of terrestrial and aquatic mobility. Results of unilateral comparisons found significant differences in male and female femoral robusticity between samples, with far north coastal Alaskans demonstrating higher robusticity than inland and coastal groups. The same results were not found in tibial samples. Neither male or female humeri show significant differences in robusticity between site types. Contrastingly, coastal male radii demonstrate increased robusticity compared to other samples. Analyses of bilateral asymmetry found significant differences in robusticity among male humeral samples, with far north coastal populations exhibiting increased asymmetry compared to other samples. Results suggest that terrestrial mobility significantly impacts femoral robusticity, but that structural optimization or ecogeographical constraints may limit the adaptive capacity of the tibia. In contrast, specific muscle activation during riverine and coastal rowing may explain why radial, but not humeral, robusticity increases among populations with aquatic mobility. Finally, hunting style utilizing harpoons and spears likely explains the increased humeral asymmetry of far north coastal males relative to coastal and inland groups.